Development of Conceptual Design for Electric Bus Body Structure Using Simple Structural Surface Method - Haryanto, Ismoyo; Widodo, Achmad; Satya, Ibrahim; Haryadi, Gunawan; Kurdi, Ojo; Budiman, Bentang; Santosa, Sigit (http://dx.doi.org/10.31427/IJSTT.2021.4.1.3, 2021)
An optimum design for a vehicle structure is always desired because the structure can significantly affect the vehicle's performance. However, some complex iterations are usually involved in the designing process. The objective of the present study is to implement the Simple Structural Surfaces (SSS) method for analyzing electric bus body structure that can reduce complexity in the stage of conceptual design. The SSS method model the vehicle structure as several planar sheets and determine the forces in each sheet. Implementing the SSS method at the early stage of the vehicle's development can minimize the number of parameter changes needed during the late stage of development. The results showed that compared with the results obtained from FEM, the SSS method gave the maximum stress value on the chassis in good accordance. Yet, the downside of using this method is that determining the deflections in the structure becomes a little bit complicated. Successfully implementing this strategy can reduce the time and cost required to develop an effective vehicle structure.